Islay : a novel - Bullard, Douglas (Gallaudet classics in deaf studies ;, 2013)
Islay is the name of an imaginary island state coveted by Lyson Sulla, a Deaf man who is tired of feeling that "hearing think deaf means dumb, pat head." Sulla signs this to his wife Mary in explanation of his desire to turn Islay into a state solely for Deaf people, with himself as governor. From there, his peripatetic quest begins. Sulla initiates his plan by driving to Islay to survey the lay of the land. There, he meets Gene Owls, another Deaf man who also has designs on the island. Sulla then embarks on travels around the nation recruiting Deaf people to join his crusade. Along the way, he meets a Deaf doctor, a bowling alley owner, a family of peddlers, a Deaf minister, and a willing businessman. Far from a heroic character, Sulla engages in each encounter in an earthy, self-serving fashion that sends up all parties involved, hearing and Deaf.